Homotypic Cancer Cell Membranes Camouflaged Nanoparticles for Targeting Drug Delivery and Enhanced Chemo-Photothermal Therapy of Glioma - Yajing Ren; Chenlin Miao; Liang Tang; Yuxiang Liu; Pinyue Ni; Yan Gong; Hui Li; Fuxue Chen; Shini Feng (MDPI AG, 2022)
Glioma is among the deadliest types of brain cancer, for which there currently is no effective treatment. Chemotherapy is mainstay in the treatment of glioma. However, drug tolerance, non-targeting, and poor blood-brain barrier penetrance severely inhibits the efficacy of chemotherapeutics. An improved treatment method is thus urgently needed. Herein, a multifunctional biomimetic nanoplatform was developed by encapsulating graphene quantum dots (GQDs) and doxorubicin (DOX) inside a homotypic cancer cell membrane (CCM) for targeted chemo-photothermal therapy of glioma. The GQDs with stable fluorescence and a superior light-to-heat conversion property were synthesized as photothermal therapeutic agents and co-encapsulated with DOX in CCM. The as-prepared nanoplatform exhibited a high DOX loading efficiency. The cell membrane coating protected drugs from leakage. Upon an external laser stimuli, the membrane could be destroyed, resulting in rapid DOX release. By taking advantage of the homologous targeting of the cancer cell membrane, the GQDs/DOX@CCM were found to actively target tumor cells, resulting in significantly enhanced cellular uptake. Moreover, a superior suppression efficiency of GQDs/DOX@CCM to cancer cells through chemo-photothermal treatment was also observed. The results suggest that this biomimetic nanoplatform holds potential for efficient targeting of drug delivery and synergistic chemo-photothermal therapy of glioma.